Deutschland-Bilder. Imagologische und kulturgeschichtliche Perspektiven - Nell, Werner (Studia Germanica Posnaniensia, 2017)
Like all those pictures of other countries, which are treated in imagological research, images of Germany are also complex, mediated by social history and historical experience, misunderstanding, misrepresentation and ideological assumptions. On the whole, these images represent the expectations and experiences of the observer even as they can truly be connected with the history, or social and cultural affairs, of the population. Thus, these images appear to be reversible figures that are simultaneously true and the products of subjective perception.